REBT Based on Music Religion and Relaxation to Develop Meaningfulness of Life - Japar, Muhammad; Purwati,; Lianasari, Dewi; Ari Suryawan, (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the influence of REBT group counselling based on music and relaxation to help teenagers develop and determine ways of being useful to society. The study design was single-subject designs with a total of 40 teenagers in 4 groups used as research subjects. Each group was provided with a REBT counselling intervention based on religious music and relaxation, with leaders and co leaders. Data collection was conducted using a scale of meaningfulness of life that has been tested for validity and reliability. While the ANOVA repeated measure and calculations using SPSS were used for data analysis. The results showed that the REBT counselling group influenced the meaning of teenager life with gender differences. Research proved that female has a higher meaningfulness in life than male.